Securing Telecommunication Based On Speaker Voice As The Public Key. - Enayah, Monther Rateb; Samsudin, Azman (Dr. Sang H. Lee, 2007)
This paper proposes a technique to generate a public cryptographic key from user’s voice while speaking over a handheld device. Making use of the human intelligence to identify authenticate the voice of the speaker and therefore use the voice as the public key. The generated public key is used to encrypt of the transferred data over the open communication channel.